Guide to participatory tools - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
A guidebook that resulted from the research project, “Stakeholders and Biodiversity in the Forest at the Local Level,” second of two initiatives between SDC and CIFOR that have worked to improve people’s livelihoods and contribute to sustainable forest through action research. The contents of the Guide to Participatory Tools, however, are the result of many years of adapting, developing and testing participatory tools by CIFOR researchers and collaborators.